2022
DOI: 10.22452/jdbe.vol22no2.3
|View full text |Cite
|
Sign up to set email alerts
|

The New Normal for Architecture Design Studio: Conceptualizing a Design Implementation Model

Abstract: Architectural design studios are the crux and core of architecture education. The closure of face-to-face Design studios due to the COVID-19 pandemic during the years 2020 and 2021 has indeed posed a set of challenges to architectural education. Through a rigorous set of research methods, the paper investigates the various possibilities and perspectives of making the challenges into opportunities to rethink, innovate and move on. The paper aims to develop a model for implementing studio-based learning innovati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The rest of the country contributed one each on the framework formulation for post-COVID-19 studio education from Malaysia by Srirangam and Ng (2022). From Spain, Fonseca et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rest of the country contributed one each on the framework formulation for post-COVID-19 studio education from Malaysia by Srirangam and Ng (2022). From Spain, Fonseca et al .…”
Section: Resultsmentioning
confidence: 99%
“…The rest of the country contributed one each on the framework formulation for post-COVID-19 studio education from Malaysia by Srirangam and Ng (2022). From Spain, Fonseca et al (2021) identified and improved essential areas that determine usability and space understanding in the user's engagement with VR environments applied to architectural and urban design, virtually exploring scenes that would not be conceivable.…”
Section: Quantitative Partmentioning
confidence: 99%
See 1 more Smart Citation